2017
DOI: 10.1111/head.13211
|View full text |Cite
|
Sign up to set email alerts
|

CGRP and PTX3 as Predictors of Efficacy of Onabotulinumtoxin Type A in Chronic Migraine: An Observational Study

Abstract: These results show that molecular markers of trigeminovascular activation (CGRP) and endothelial dysfunction (PTX3) are associated with response to OnabotA and may act as new biomarkers for the selection of treatment in chronic migraineurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
77
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(89 citation statements)
references
References 36 publications
(85 reference statements)
8
77
2
2
Order By: Relevance
“…Inflammation is present in migraine . Previously, our group showed that chronic migraineurs had elevated IL‐6 levels and lower IL‐10 levels compared with individuals without headache . We confirmed this observation in our cohort of participants, in which the chronic migraine group presented more IL‐6 and less IL‐10 in comparison with the control group.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Inflammation is present in migraine . Previously, our group showed that chronic migraineurs had elevated IL‐6 levels and lower IL‐10 levels compared with individuals without headache . We confirmed this observation in our cohort of participants, in which the chronic migraine group presented more IL‐6 and less IL‐10 in comparison with the control group.…”
Section: Discussionsupporting
confidence: 89%
“…Particularly, it has been shown that chronic migraineurs have interictal elevated circulating levels of CGRP . For instance, onabotulinumtoxin A (OnabotA), a common treatment option for chronic migraine, is capable of reducing interictal CGRP serum levels and it could be a predictor of good response to this therapy …”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, reduced sensitivity to molecules that activate C‐meningeal nociceptors through TRPV1 and TRPA1 and reduce the CGRP release might contribute to the clinical efficacy of BTX‐A in migraine. In people with CM, an effective treatment was correlated with higher serum CGRP levels, 76,77 that decrease in the interictal phase 73 . These results assume that the effectiveness of BTX‐A depends on the inhibition of CGRP release from peripheral sensory afferents and the consequent reduction of its serum level.…”
Section: Btx‐a and The Cgrp Pathwaymentioning
confidence: 81%
“…Seeking clinical biomarkers that may contribute to predict how our patients will evolve is an important goal for physicians since it helps to manage both patient and physician’s expectations, better understand the mechanisms of CM, and optimize the therapeutic resources . So far, most predictors of response to OnabotulinumtoxinA are not only based on clinical features, but also in molecular biomarkers such as calcitonin gene‐related peptide (CGRP) . However, results are limited or controversial, and are based on the presence of a good response (>50%).…”
Section: Introductionmentioning
confidence: 99%
“…16 So far, most predictors of response to OnabotulinumtoxinA are not only based on clinical features, [17][18][19][20][21] but also in molecular biomarkers such as calcitonin gene-related peptide (CGRP). [22][23][24] However, results are limited or controversial, and are based on the presence of a good response (>50%).…”
Section: Introductionmentioning
confidence: 99%